Інвестиційна привабливість інтелектуального капіталу підприємств: ідентифікація та діагностика - Хілуха (Ліпич), Оксана Анатоліївна; Ліпич, Любов Григорівна; Товстенюк, Олександр Віталійович; Khilukha, Oksana A.; Lipych, Liubov H.; Tovsteniuk, Oleksandr V. (Хмельницький національний університет, 2014)
У статті досліджений процес діагностики інвестиційної привабливості інтелектуального капіталу підприємств. Для ефективної діагностики інтелектуального капіталу машинобудівних підприємств потрібно визначити її цілі, проаналізувати фактори, що впливають на діагностику, визначити показники, що дозволять оцінити інвестиційну привабливість інтелектуального капіталу підприємств. Intellectual capital is the value of a company or organization's employee knowledge, business training and any proprietary information that may provide the company with a competitive. For complex firms in today’s creative economy, this infers that intellectual capital – an induced managerial capacity to search for novel ways to create value Is rapidly becoming liabilities unless it is innovatively managed for overcoming the inertia of discontinuity opportunities. The aims of the research are to explore the diagnose process of the investment attractiveness of the enterprise intellectual capital. In the article it was systemized the factors of the influence on the investment attractiveness. The author established the indicators of the intellectual capital and determined the investment strategy goals. In the result it was identified the diagnose process of the investment attractiveness of the enterprise intellectual capital.
The investment attractiveness of the enterprise intellectual capital: diagnosis and identification
Keywords: інтелектуальний капітал; інвестиційна привабливість підприємства; діагностика; diagnostics; the investment attractiveness of the enterprise intellectual capital